2009
DOI: 10.1007/s00277-009-0834-3
|View full text |Cite
|
Sign up to set email alerts
|

Levels of angiogenic factors in patients with multiple myeloma correlate with treatment response

Abstract: Angiogenesis plays a significant role in the pathogenesis of multiple myeloma (MM). We have measured concentrations of angiogenesis activators, including vascular endothelial growth factor (VEGF), basic fibroblast growth factor, and hepatocyte growth factor (HGF), and inhibitors, including endostatin, thrombospondin-1 (TSP-1), and angiostatin in the peripheral and bone marrow blood of MM patients at diagnosis and after high-dose chemotherapy. We have analyzed 96 patients with secretory MM. Serial measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
3
22
0
1
Order By: Relevance
“…In multiple myeloma, vascular endothelial growth factor was produced by malignant plasma cells and stimulates the proliferation of endothelial cells, also at the same time, vascular endothelial growth factor had secreted by endothelial cells in the tumor microenvironment it acted in an autocrine and paracrine way on both endothelial and myeloma cells, so there was a reciprocal stimulation between endothelial cells and myeloma cells to produce it [12] . A significant increment in plasma level of vascular endothelial growth factor and its soluble receptor -2 in myeloma patients at diagnosis before starting chemotherapy protocol with significant decrement in there plasma levels after four courses of VAD protocol of therapy in responded patients and this was consistent with same data observed by Mileskhin et al who reported that high levels of vascular endothelial growth factor were associated with response rate in patients treated chemotherapy [13,16] . Anther contradictory results were detected by Cibeira and collaborators who noticed that there was not a significant correlation between response rate and vascular endothelial growth factor level or its receptor-2 [14,15] and this might attributed to different in selection criteria of patients or method of assessment as the concentrations of angiogenesis factors in the plasma rather than in the serum because platelets contain significant concentrations of these cytokines, released during during preparation of serum [6,17] .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In multiple myeloma, vascular endothelial growth factor was produced by malignant plasma cells and stimulates the proliferation of endothelial cells, also at the same time, vascular endothelial growth factor had secreted by endothelial cells in the tumor microenvironment it acted in an autocrine and paracrine way on both endothelial and myeloma cells, so there was a reciprocal stimulation between endothelial cells and myeloma cells to produce it [12] . A significant increment in plasma level of vascular endothelial growth factor and its soluble receptor -2 in myeloma patients at diagnosis before starting chemotherapy protocol with significant decrement in there plasma levels after four courses of VAD protocol of therapy in responded patients and this was consistent with same data observed by Mileskhin et al who reported that high levels of vascular endothelial growth factor were associated with response rate in patients treated chemotherapy [13,16] . Anther contradictory results were detected by Cibeira and collaborators who noticed that there was not a significant correlation between response rate and vascular endothelial growth factor level or its receptor-2 [14,15] and this might attributed to different in selection criteria of patients or method of assessment as the concentrations of angiogenesis factors in the plasma rather than in the serum because platelets contain significant concentrations of these cytokines, released during during preparation of serum [6,17] .…”
Section: Discussionsupporting
confidence: 88%
“…Anther contradictory results were detected by Cibeira and collaborators who noticed that there was not a significant correlation between response rate and vascular endothelial growth factor level or its receptor-2 [14,15] and this might attributed to different in selection criteria of patients or method of assessment as the concentrations of angiogenesis factors in the plasma rather than in the serum because platelets contain significant concentrations of these cytokines, released during during preparation of serum [6,17] . Vascular endothelial growth factor and its soluble receptor -2 in myeloma patients had associated with other poor prognostic factors and both of them had independent risk factors with a predictive value due to significant decrement in there plasma level after four courses of VAD protocol of therapy in responded patients reflecting decrement of angiogenesis rate in myeloma patients after therapy [16] . The aim of front-line therapy for multiple myeloma was to substantially decrease tumor burden and the degree of disease Variables VEGF(pg/mL) Before Therapy After Therapy P value VEGFR-2(ng/mL) Before Therapy After Therapy P value Variables albumin<3.5 g/dL β2microglobulin ≥5.5μg/mL Creatinine ≥2 mg/dL VEGF (pg/mL) at diagnosis ≥40 VEGFR-2 (ng/mL) at diagnosis ≥10 reduction is associated with improved outcome, including prolonged progression-free survival (PFS) and overall survival (OS) [17] .…”
Section: Discussionmentioning
confidence: 96%
“…Hypoxic factors such as NO are capable inducers of angiogenesis, and NO signaling through PKG has been linked to insulin-induced production of vascular endothelial growth factor (VEGF-1) in smooth muscle cells (24). This potent angiogenic factor is also secreted by MM cells in response to IGF-1 stimulation, and increased VEGF-1 serum levels are correlated with poor prognosis in MM patients (25,26). Interestingly, malignant MM PC express high levels of nitrotyrosine, a marker of NO presence, and NOsynthase 1, 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple therapies targeting either the CNS or CLL have been used with variable results in terms of rate and duration of response. 4,5 Outcome after CNS treatment is not established and controversies persist about the need to control the systemic CLL.…”
Section: 11mentioning
confidence: 99%
“…1 HGF and HGF receptor protein (MET) have been implicated in myeloma pathogenesis based on the observation that elevated HGF levels are associated with worse prognosis [2][3][4] and lack of response to chemotherapy. 5,6 In addition, MM cells express HGF, creating a putative autocrine HGF/MET loop. [7][8][9] In vitro models demonstrated myeloma cell growth inhibition through MET or HGF inhibition.…”
mentioning
confidence: 99%